Fundamentals of optical fiber sensors - Fang, Zujie, 1942-; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2012)
'This book describes the latest development in optical fiber devices, and their applications to sensor technology'--
Fundamentals of Optical Fibers -- Fiber Sensitivities and Fiber Devices -- Fiber Gratings and Related Devices -- Distributed Optical Fiber Sensors -- Fiber Sensors with Special Applications -- Extrinsic Fiber Fabryb6(BPerot Interferometer Sensor.s
Includes bibliographical references and index.
Print version record.
Keywords: Optical fiber detectors; Fiber optics; Optical fiber detectors; Fiber optics; Electronic books